ANALISIS KETERAMPILAN BERPIKIR KOMPUTASIONAL SISWA DALAM MENYELESAIKAN PROYEK PEMROGRAMAN ( Studi Kasus di Kelas X SMA Kristen Citra Bangsa ) - Natapuling, Lukas Feri; Maria Magdalena Beatrice Sogen; Diana Yanni Ariswati Fallo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Lukas Ferry Natapuling, 2026. Analysis of Students’ Computational Thinking Skills in Completing Programming Projects (A Case Study of Grade X Students at Citra Bangsa Christian Senior High School). Informatics Education Study Program, Faculty of Teacher Training and Education, Citra Bangsa University. Supervisor I: Dr. Maria M. B. Sogen, S.Kom., M.Pd., Supervisor II: Diana Yanni Ariswati Fallo, S.Kom., M.T. This study aims to describe the computational thinking processes of Grade X students at Citra Bangsa Christian Senior High School in completing programming projects and to identify the challenges and strategies used by students to overcome difficulties during the process. Computational thinking is an essential 21st-century skill that includes decomposition, pattern recognition, abstraction, and algorithmic thinking. These skills are necessary to help students solve problems logically, systematically, and effectively in informatics learning. This research employed a qualitative approach using a case study design. The research subjects were Grade X students of Citra Bangsa Christian Senior High School selected through purposive sampling based on their active involvement in programming projects. Data were collected through observation, semi-structured interviews, and documentation. Data analysis was conducted using the Miles and Huberman model, which consists of data reduction, data display, and conclusion drawing. Data validity was ensured through source and technique triangulation. The findings indicate that students applied various aspects of computational thinking in completing programming projects, although their level of mastery varied across different aspects. Decomposition and pattern recognition were evident in students’ ability to break down problems and identify similarities in solution procedures. However, abstraction and algorithmic thinking remained challenging for some students, particularly in filtering relevant information and developing systematic solution steps. The challenges encountered included difficulties in understanding programming logic, determining appropriate algorithms, and resolving program errors. To overcome these challenges, students employed several strategies, such as discussing problems with peers, consulting teachers, searching for references on the internet, and using trial-and-error methods. This study provides a deeper understanding of students’ computational thinking processes and may serve as a reference for teachers in designing more effective and student-centered informatics learning experiences.